2015
DOI: 10.1371/journal.pone.0117563
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Responses and Prediction of Peak Oxygen Uptake during the Shuttle Walking Test in Healthy Sedentary Adult Men

Abstract: BackgroundThe application of the Shuttle Walking Test (SWT) to assess cardiorespiratory fitness and the intensity of this test in healthy participants has rarely been studied. This study aimed to assess and correlate the cardiorespiratory responses of the SWT with the cardiopulmonary exercise testing (CEPT) and to develop a regression equation for the prediction of peak oxygen uptake (VO2 peak) in healthy sedentary adult men.MethodsIn the first stage of this study, 12 participants underwent the SWT and the CEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…Many authors have focused on developing predictive equations from submaximal tests or their ability to accurately identify CRF in healthy and disabled population [ 5 11 , 14 , 15 ]. Neves et al (2015) [ 7 ] found that maximal cardiorespiratory responses in the shuttle walk test agreed with those obtained in the CPX, and the developed equation showed viability for the prediction of VO 2peak in healthy sedentary men. Moreover, as in our study, BMI and the functional test performance, on that occasion the gait speed, explained 40.6% (p = 0.001) of the variance in VO 2peak .…”
Section: Discussionmentioning
confidence: 85%
“…Many authors have focused on developing predictive equations from submaximal tests or their ability to accurately identify CRF in healthy and disabled population [ 5 11 , 14 , 15 ]. Neves et al (2015) [ 7 ] found that maximal cardiorespiratory responses in the shuttle walk test agreed with those obtained in the CPX, and the developed equation showed viability for the prediction of VO 2peak in healthy sedentary men. Moreover, as in our study, BMI and the functional test performance, on that occasion the gait speed, explained 40.6% (p = 0.001) of the variance in VO 2peak .…”
Section: Discussionmentioning
confidence: 85%
“…The test was terminated when the volunteer was not able to maintain the required speed (more than 0.5 m from the cone), at the request of the volunteer, or because of some other reported symptom (dyspnea, dizziness, vertigo, angina). As suggested by the literature, we used a protocol of 15 levels to evaluate the maximum cardiorespiratory capacity of healthy participants (27). Before and after the test, the heart rate (HR, measured by a heart rate monitor), blood pressure (measured by a mercury sphygmomanometer cuff and a stethoscope) and rating of perceived exertion (RPE, Borg scale, range 6–20) were measured.…”
Section: Methodsmentioning
confidence: 99%
“…The CPET was discontinued, when the respiratory exchange ratio ≥1.10 and the HR reached to 85% of max HR. [18] The maximal oxygen consumption (VO 2 max in milliliters per kilogram per min) reached at the end of exercise test was directly measured by ergospirometry analyzer was recorded.…”
Section: Assessmentmentioning
confidence: 99%